Eco-environmental effect and driving factors of changing “production-living-ecological space” in northern Xinjiang, China - Wang, Yin; Wang, Yang; Xu, Wenzhe; Sheng, Ziyi; Zhu, Zhen; Tang, Haisheng (Frontiers in Ecology and Evolution, 2023)
Exploring the ecological and environmental effects of "production-living-ecological space" (PLES) evolution and its driving factors can provide a scientific basis for the implementation of territorial spatial planning and ecological environmental protection. Taking the region north of the Tianshan Mountains in Xinjiang, China, as our study area, we analyze the spatial and temporal variations of the ecological and environmental effects of PLES evolution from 2000 to 2020. To do so, we apply the grid cell method, the ecological and environmental quality index, the global autocorrelation model, and the kernel density estimation. Additionally, we use a geographic detector model to reveal the drivers of spatial variation in ecological and environmental quality. Results showed from 2000 to 2020, PLES in the study area is mainly ecological accommodation land. However, there is an obvious trend showing a decrease in ecological accommodation land area and an increase in other land types. Production land and living land increased the most, among which agricultural land and industrial land were mainly converted from grassland ecological land and water ecological land, respectively. The quality of the ecological environment is basically stable during the study period, with an overall slight declining trend, which indicates the quality of ecological environment has decreased slightly. The spatial distribution of the eco-environmental effect shows a significant spatial autocorrelation pattern of "dense in the west and sparse in the east", along with a spatial clustering phenomenon. The main factors of spatial variation in ecological quality is elevation, and the interactions between the factors are mainly non-linearly and double-factor enhanced. The spatial differentiation of ecological environmental quality in the study area is the result of multiple factors.